Modified emission of polymer films by ultrathin Ag nanoparticle films. (November 2018) - Wang, Qingru; Zheng, Shiling; Shi, Qiang; Zhang, Dong; Wang, Wenjun; Han, Lin
Abstract: Thin nanoparticle films with tunable and broad surface plasmonic absorption were obtained by disintegrating Ag films upon thermal annealing. The Ag thin film deposited by Physical Vapor Deposition (PVD) system was turned into the Ag particle film after annealing. The Ag particle films can be used as an enhanced fluorescence substrate. In this work, the emission of polymer films at 620 nm was tuned by the Ag particle films we prepared. The enhancement of fluorescence depends on the distribution of the particle films, i.e. the size of particles and the distance between particles. The maximum enhancement of fluorescence was nearly 9 folds. We attributed the enhancement of fluorescence to the enhanced local field induced by the Local surface plasmon resonance (LSPR) of nanoparticles. The local field in presence of Ag nanoparticles was calculated by using the finite-difference-time-domain (FDTD) method, the theoretical results agreed with the experimental results. Highlights: We report a facile approach to obtain the Ag nanoparticle films by annealling Ag thin films. The luminescence enhancement is obtained by using the Ag nanoparticles films in presence of Ag nanoparticles. The enhancement of fluorescence depends on the size of nanoparticles and the spacing between nanoparticles.